2008
DOI: 10.1016/j.jpcs.2008.06.041
|View full text |Cite
|
Sign up to set email alerts
|

Momentum-resolved charge excitations in high-Tc cuprates studied by resonant inelastic X-ray scattering

Abstract: We report a Cu K-edge resonant inelastic x-ray scattering (RIXS) study of high-Tc cuprates. Momentum-resolved charge excitations in the CuO2 plane are examined from parent Mott insulators to carrier-doped superconductors. The Mott gap excitation in undoped insulators is found to commonly show a larger dispersion along the [π, π] direction than the [π, 0] direction. On the other hand, the resonance condition displays material dependence. Upon hole doping, the dispersion of the Mott gap excitation becomes weaker… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…On the other hand, the spectral weight increases almost at the same energy with doping at high |q || | and high energy, for example, h > 0.2 for q || = (h,0) and above 1 eV. The latter has been confirmed by the K-edge RIXS [22,25]. This doping evolution is reproduced in the theoretical calculation of the dynamical charge correlation function, N(q,ω) [See Supplementary Fig.…”
Section: Resultsmentioning
confidence: 53%
“…On the other hand, the spectral weight increases almost at the same energy with doping at high |q || | and high energy, for example, h > 0.2 for q || = (h,0) and above 1 eV. The latter has been confirmed by the K-edge RIXS [22,25]. This doping evolution is reproduced in the theoretical calculation of the dynamical charge correlation function, N(q,ω) [See Supplementary Fig.…”
Section: Resultsmentioning
confidence: 53%
“…6 which is consistent with the case of La 2Àx Sr x CuO 4 . A small dispersion was also observed in Ca 1:8 Na 0:2 CuO 2 Br 2 , 85) which is shown in Fig. 8(b).…”
Section: Cupratesmentioning
confidence: 61%
“…They measured the Mott gap excitation in Ca 2 CuO 2 Cl 2 , which is a parent material of high-T c superconducting cuprates, and found that the energy of the Mott gap excitation is lowest at the zone center of the CuO 2 plane and the magnitude of the dispersion along the ½; direction is larger than that along the ½; 0 direction. Following this work, other parent compounds were studied, including La 2 CuO 4 , 81-84) Nd 2 CuO 4 , 85,86) and YBa 2 Cu 3 O 6 . 85) In Fig.…”
Section: Cupratesmentioning
confidence: 99%
See 2 more Smart Citations